Innovation of Elderly in Care Sticks in Maintaining Elderly Walking Balance and Speed - Jusuf Kristianto; Ni Made Riasmini; Eviana Sumarti Tambunan; Sri Djuwitaningsih; Nur Rachmat; Fajar Susanti (Syntax Corporation Indonesia, 2022)
The study of balance in the elderly is a serious concern. Even the main goal of rehabilitation for elderly people who have fallen is to improve balance. The need for a simple, fast, and accurate balance-checking tool is expected to help the elderly rehabilitation program. The purpose of this research is to produce Assistive Technology in fulfilling ADL to reach the SMART elderly. Research Methods This type of research is a cross-sectional study with observational (survey). Observation of balance in the elderly with two measuring devices, namely balance and walking speed. This research was conducted at the Tresna Werda Nursing Home Jakarta in August 2022. The number of residents of the Tresna Werda Jakarta Nursing Home who participated in the inclusion and exclusion criteria selection was 30 people consisting of 10 (35%) men and 30 ( 65 %) females. The elderly who have fulfilled the inclusion and exclusion criteria become research subjects. In this study of the elderly using the I Care Stick, the results were better than the ordinary stick with a significance of 0.001. The average speed of respondents walking using the I Care Stick was 28.47 seconds and the normal walking stick was 31.87 seconds. In this study, it was found that the balance of the elderly who used the I Care Stick was more stable than the elderly who walked using a regular cane with a significance of 0.001, with the average slope that occurred on the I Care Stick at 21.13 seconds and the regular cane at 10.53. The elderly who used the I Care Cane significantly (p-value: 0.001) seemed to walk better than the regular cane with an average speed of 34.70 seconds, while the average speed of the cane was 42.80 seconds. The balance of the elderly who uses the I Care Cane is very significant compared to the elderly who walks using a regular cane.